Languange Variation in the Digital Era: The Influence of Tiktok Content and Interaction on The Formation of Social Dialects Among Indonesian - Atika Anjani; Khairunnisa Azzahra; Novani Elisabeth Lingga; Nurhikmah Siagian; Resa Aquilera Ramadhani; Meisuri Meisuri (CV. Rayyan Dwi Bharata, 2025)
This study explores how TikTok functions as a digital linguistic arena that shapes the emergence of social dialects among Indonesian youth. Far beyond a platform for entertainment, TikTok facilitates the creation, dissemination, and reinforcement of new linguistic patterns through video content, captions, and interactive comments. Guided by Labov’s Variationist Sociolinguistics (1972), this research employs a qualitative descriptive approach by analyzing 15 TikTok videos and 100–150 user comments. The analysis focuses on linguistic features such as slang, code-switching, and identity markers that reflect youth identity and social belonging. The findings reveal that TikTok fosters rapid linguistic innovation such as slang expressions like receh banget and ngakak brutal, English borrowings such as slay and literally, and fandom or regional identity markers that demonstrate how users blend local and global influences. These linguistic practices not only strengthen community solidarity but also signify how digital spaces accelerate the evolution of language variation. Overall, the study concludes that TikTok represents a dynamic sociolinguistic ecosystem where technology, culture, and identity intersect, highlighting the platform’s crucial role in redefining Indonesian youth’s linguistic expression in the digital age